Participação dos receptores GABAa no potencial excitatório pós sinápitco em hipocampo e amigdala de ratos wistar audiogênicos (WAR) - Luciana Estefani Drumond de Carvalho (2007)
Epilepsies are brain disorders characterized by recurrent andspontaneous crises. They are caused by hyper-synchronized discharges,localized or generalized through the brain. Their high incidence and prevalence are responsible for both psycho and social impact. An important class of epilepsy is the reflex epilepsy, initiated by exposure to sensory stimulus. The audiogenic crises, a modality of reflex epilepsy, are related to dysfunction of the auditory pathway. The selection of WAR (Wistar Audiogenic Rats) lineage is based on crises susceptibility induced due to the exposure to the high intensity sound stimulus. Nevertheless these animals show greater sensibility to crises when exposed to other convulsive agents such as electroshock, pentyleneterazole and pilocarpina, suggesting changes on their neuronalnetwork.We study the excitatory post-synaptic potential (EPSP) pattern in the presence and absence of picrotoxin (which blocks the GABAA receptors) in the hippocampus and amygdala of WAR lineage. We also analyze the induction of plastic modifications in the lateral amygdala, in presence or absence of picrotoxin. The results show a reduced response to the toxin, suggesting alteration on the GABAA tonus. In the hippocampus, this points to a generalized dysfunction of the neuronal substrates, but there is no evidence of involvement of such structure in audiogenic crises. Our results also show a tendency to increase in the basal response when compared to the control, suggesting a neuronal circuit more excitable and prone to epileptic crises. We did not observe a low or even standing potentiation in the amygdala, probably caused by its increased and saturated basal response and by a reduced excitatorymodulation. In presence of picrotoxin LTP was not observed for WAR or Wistar group. The inhibitory effect of picrotoxin in EPSP on the amygdala is followed by a recovery response to basal levels, similar to the increase observed for LTP. We conclude that WAR show a GABAA system alteration leading to a hyperexcitability of their neuronal circuits. These animals also behave as resistant Wistar rats when their GABA A system is blocked.